LOYALITAS PELANGGAN HOTEL BUDGET: PERAN KUALITAS PELAYANAN DAN KEPUASAN WISATAWAN - Kusyana, Dewa Nyoman Benni (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to examine the effect of service quality on customer loyalty by adopting two approaches: behavioral loyalty and attitudinal loyalty, with customer satisfaction serving as a mediating variable. The study was conducted in Denpasar City, involving 160 tourists staying at budget hotels, with an unknown population size. The sample was determined using the accidental sampling technique. The data collection instrument was a questionnaire with a five-point Likert scale. To analyze the relationship between variables and test the hypothesis, path analysis was employed using SPSS software. The study's results showed that service quality and customer satisfaction have a direct, positive, and significant effect on both behavioral loyalty and attitudinal loyalty. Additionally, service quality has been shown to increase customer satisfaction directly. The mediation test revealed that customer satisfaction acts as a mediator in the relationship between service quality and the two dimensions of loyalty.